Corporate income tax competition, double taxation treaties, and foreign direct investment - Eckhard Janeba (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
In the presence of international-capital mobility foreign direct investment is influenced by corporate income taxation and the rules how taxes paid in the host country are treated at home. In this paper the exemption, credit and deduction method are considered as tax rules. First, it is shown that under the exemption method there exist tax rate combinations that lead to a reversal of capital flows compared to a free-trade situation. Second, the decision on the tax rule and the corporate tax rate is endogenized as outcome in a non-cooperative game. All tax rules lead to the same inefficient outcome. Therefore, for each tax rule we analyze the conditions for Pareto-improving tax cooperation. It is shown that only the credit method requires neither compensatory payments nor fully harmonized tax rates.
Keywords: F20; H87; 330